1994
DOI: 10.1590/s1516-31801994000100004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of functional capacity during gait using a reciprocal propulsion orthosis (ARGO): a comparative study with a conventional mechanical orthosis

Abstract: One subject (male, 24 years) with an incomplete motor and sensitive SCI, neurological level C6-C7 was submitted to a comparative study during gait using an advanced reciprocating gait othosis (ARGO) and a conventional mechanical orthosis (CMO) and respiratory and metabolic variables were compared at peak effort and in the second minute of recovery. We found that the ARGO, as with the CMO, not guarantee gait independence but the ARGO does enable a more functional gait pattern with a more efficient ventilation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The two poor-quality studies in this group according to PEDro scale (1/10) performed by Middleton et al 30 and Muszkat et al 31 Middleton et al 30 in a comparison between different types of medial linkage orthoses on one SCI subject from C6 level of injury showed that there was no significant difference between the Moorong and WO in PCI values when walking along a level surface (11.5 beat per m); however, the Moorong orthosis provided increased speed of walking compared with WO during ambulation. Muszkat et al 31 in a comparison between ARGOs and HKAFOs in one SCI subject with C6 level of injury reported that the ARGO needed less energy expenditure during ambulation (0.9 versus 0.82).…”
Section: The Effect Of Mechanical Orthoses On Energy Consumption In Pmentioning
confidence: 98%
See 1 more Smart Citation
“…The two poor-quality studies in this group according to PEDro scale (1/10) performed by Middleton et al 30 and Muszkat et al 31 Middleton et al 30 in a comparison between different types of medial linkage orthoses on one SCI subject from C6 level of injury showed that there was no significant difference between the Moorong and WO in PCI values when walking along a level surface (11.5 beat per m); however, the Moorong orthosis provided increased speed of walking compared with WO during ambulation. Muszkat et al 31 in a comparison between ARGOs and HKAFOs in one SCI subject with C6 level of injury reported that the ARGO needed less energy expenditure during ambulation (0.9 versus 0.82).…”
Section: The Effect Of Mechanical Orthoses On Energy Consumption In Pmentioning
confidence: 98%
“…Muszkat et al 31 in a comparison between ARGOs and HKAFOs in one SCI subject with C6 level of injury reported that the ARGO needed less energy expenditure during ambulation (0.9 versus 0.82).…”
Section: The Effect Of Mechanical Orthoses On Energy Consumption In Pmentioning
confidence: 99%